B-cell intrinsic regulation of antibody mediated immunity by histone H2A deubiquitinase BAP1 - Liang, Yue; Wang, HanChen; Seija, Noé; Lin, Yun Hsiao; Tung, Lin Tze; Di Noia, Javier M.; Langlais, David; Nijnik, Anastasia (Frontiers in Immunology, 2024)
BAP1 is a deubiquitinase (DUB) of the Ubiquitin C-terminal Hydrolase (UCH) family that regulates gene expression and other cellular processes, through its direct catalytic activity on the repressive epigenetic mark histone H2AK119ub, as well as on several other substrates. BAP1 is also a highly important tumor suppressor, expressed and functional across many cell types and tissues. In recent work, we demonstrated a cell intrinsic role of BAP1 in the B cell lineage development in murine bone marrow, however the role of BAP1 in the regulation of B cell mediated humoral immune response has not been previously explored.In the current study, we demonstrate that a B-cell intrinsic loss of BAP1 in activated B cells in the Bap1 fl/fl Cγ1-cre murine model results in a severe defect in antibody production, with altered dynamics of germinal centre B cell, memory B cell, and plasma cell numbers. At the cellular and molecular level, BAP1 was dispensable for B cell immunoglobulin class switching but resulted in an impaired proliferation of activated B cells, with genome-wide dysregulation in histone H2AK119ub levels and gene expression. In summary, our study establishes the B-cell intrinsic role of BAP1 in antibody mediated immune response and indicates its central role in the regulation of the genome-wide landscapes of histone H2AK119ub and downstream transcriptional programs of B cell activation and humoral immunity.